PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI 008 TELUK PULAU HULU KECAMATAN RIMBA MELINTANG - Fauziah Fauziah; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low results in learning mathematics student SDN 008 Teluk Pulau Hulu Kecamatan Rimba Melintang Crossing, with an average grade of 60.00. While the value of the minimum completeness criteria (KKM) Mathematics is 68. Among the students who totaled 21 people only 8 people were reached KKM. This study is a Classroom Action Research (CAR) conducted aims to improve mathematics learning outcomes SDN 008 Teluk Pulau Hulu Kecamatan Rimba Melintang Across the implementation of Realistic Mathematics learning approach. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This paper presents the study results of the data obtained from the average of the results of study before action 60.00 increase to 5.70% to 77.30 in cycle I. In the second cycle increased to 10.3% with an average of 83.21. Teacher activity in the first cycle the first meeting to obtain a percentage of 63% in both categories, at the second meeting has increased by 71% the percentage of both categories. Selanjutya first meeting of the second cycle of teacher activity also increased with the percentage of 80% good category and at the second meeting increased again by 86% the percentage of very good category. Activity of students in the first cycle the first meeting to obtain the percentage of 61% good category, at the second meeting has increased by 69% the percentage of both categories, the students begin to understand this cycle of learning activities with the application of mathematics learning Realistic characterized by the activity of students in the second cycle increased with the first meeting the percentage of 75% both categories. At the second meeting have increased the percentage of 83% is very good category. Results of the study in Kelas V SDN 008 Teluk Pulau Hulu Kecamatan Rimba Melintang prove that the application of realistic mathematics learning approach can improve the results of learning mathematics Elementary School fifth grade students SDN 008 Teluk Pulau Hulu Kecamatan Rimba Melintang.Keywords : Implementation Approach Realistic Mathematics Education, Mathematics Learning Outcomes3